Analysis of a New Approach to Admission Call Control - Ashiesh Prakash; Amit Singhal (International Journal of Mobile Computing Technology, 2025)
This study presents a new method of managing call admission in wireless networks using a resource reservation technique. The system under study comprises a defined number of operating devices, standby units, and technicians assigned to repair failed devices. In this method, the failure and repair of devices are assumed to follow an exponential distribution. Whenever a device fails, a standby unit replaces it to maintain seamless functionality, and the failed device is forwarded to a technician group for restoration. The core idea revolves around optimizing the use of limited network resources while ensuring continuous service and minimizing call blocking. To mathematically model the system, transient state equations were developed. These equations are solved using a numerical method known as the fourth-order Runge-Kutta technique. The proposed approach demonstrates improved performance measures, including lower call blocking rates and better resource utilization. This study contributes to network performance optimization in environments where equipment reliability and user demands are dynamically changing. By simulating real-world network behavior, this model proves effective in improving Quality of Service (QoS) without compromising user satisfaction.
Keywords: Operating devices spares; Queue length; Runge-Kutta technique; device failure and recovery modeling; transient analysis